Incidencia jurídica de paternidad declarada bajo rebeldía del presunto progenitor, en el cantón Santa Rosa, período 2013-2014. - Balseca Falconí, Fernando Virgilio (2013)
In modern societies of Ecuador and the world, children / and adolescents are protected in a special way, the interests principle applies in all areas where the interests of this vulnerable group commit, especially when it comes to the right identity, hence legally exist legal mechanisms to declare paternity based on scientific evidence such as DNA testing in cases where the alleged father does not appear paternity is presumed positive and the judge finally resolved in favor of who claim paternity. This means that on the defendant in default and the child is born and the filial relationship with her birth rights and obligations such as providing food. However it is necessary to analyze the reasons for the non-appearance of the defendant and that in many cases for economic reasons or procedural errors, hence the only legal option left to the defendant to apply the universal principle of justice as to challenge the decisions of the judges. Determine the legal effect of paternity declared under rebelliousness of the alleged parent is the overall objective that moves this legal research, as well as check whether to fulfill the right of children to be recognized by the parent not being violated rights of the alleged father.